2005
DOI: 10.1262/jrd.17038
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effect of Leptin on Growth Hormone (GH)- and Insulin-Like Growth Factor-I (IGF-I)-stimulated Progesterone Secretion and Apoptosis in Developing and Mature Corpora Lutea of Pig Ovaries

Abstract: Abstract. This study was designed to determine whether leptin modulates growth hormone (GH)-and insulin like growth factor-I (IGF-I)-stimulated progesterone (P4) production by corpora lutea (CL). Luteal cells were recovered from early developing (ELP) and mature (MLP) corpora lutea and cultured in defined medium with various combinations of GH, IGF-I, and leptin (0-200 ng/ml). P4 concentrations in the media were determined after 48 h of culture. During the early luteal phase, leptin at all used doses had no ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 23 publications
1
17
0
1
Order By: Relevance
“…In preovulatory follicles, leptin acts synergistically with IGF-I on the luteinizition process, which starts just before ovulation [3]. During CL development, leptin given alone acts as an antiapoptotic factor, and when combined with IGF-I, a known antiapoptotic factor, it protects against excessive apoptosis and supports the appropriate cell numbers necessary for maintenance of homeostasis in the developing CL [4]. Studies performed mainly in rats and pigs have suggested that intraovarian IGF-I synthesis is of major importance in promoting follicular development, primarily by amplifying the actions of pituitary gonadotrophins and GH [18,19].…”
Section: Igf-i and Leptin Receptorsmentioning
confidence: 99%
See 2 more Smart Citations
“…In preovulatory follicles, leptin acts synergistically with IGF-I on the luteinizition process, which starts just before ovulation [3]. During CL development, leptin given alone acts as an antiapoptotic factor, and when combined with IGF-I, a known antiapoptotic factor, it protects against excessive apoptosis and supports the appropriate cell numbers necessary for maintenance of homeostasis in the developing CL [4]. Studies performed mainly in rats and pigs have suggested that intraovarian IGF-I synthesis is of major importance in promoting follicular development, primarily by amplifying the actions of pituitary gonadotrophins and GH [18,19].…”
Section: Igf-i and Leptin Receptorsmentioning
confidence: 99%
“…The authors thank Dr B. Szafranska (University of Warmia and Mazury, Olsztyn, Poland) for the generous gift of P 4 …”
Section: Acknowledgmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the role of leptin in CL is restricted to the period of the luteal phase. Leptin protects luteal cells from excessive apoptosis and supports an appropriate cell number, which is necessary for maintenance of homeostasis in developing CL (Gregoraszczuk & Ptak, 2005). Fig.…”
Section: Leptinmentioning
confidence: 99%
“…Schematic summarizing leptin effect on steroid secretion in porcine ovary. (─) no effect, (↑) stimulatory effect, and (↓) inhibitory effect (Gregoraszczuk et al, 2004(Gregoraszczuk et al, , 2005(Gregoraszczuk et al, , 2006 Evidence has also emerged indicating a potential direct role for leptin in the regulation of mammalian oocyte and preimplantation embryo development. Leptin and its receptor have been observed by immunoblotting and immunohistochemistry methods to be present in the secretory endometrium and preimplantation embryos.…”
Section: Leptinmentioning
confidence: 99%